FitAlert enhancing the health, wellness and well-being to the community – A conceptual enchance business model - Che Bakar, Muhamad Nasrul Faiz; A.Hamid, Muhammad Afiq; Ruzman, Muhammad Izzuddin; Ahmad Dahlan, Abdul Rahman (Research Publish Journal, 2018)
The paper reviews about the conceptual combination of fitness, community and lifestyle application named FitAlert, this app help eases the users in their fitness life and also be involve in the fitness community all around the country. In addition, this app provides an advertisement about fitness event in Malaysia, and also provide exercise tutor for users. This app also has other function such as giving the users a reward for completing the challenges given. The app also provides a platform that allow users to join and register for an advertised event such as running event, workout event, bicycle event and many more. Besides that, this app also has a website page for the users to review the event for more detail. In premium version, there will be an extra function and features for users to enjoy, for example, users can compete with other users in leaderboard, and collect more rewards. Lastly, the app is collaborating with a fitness event organizer for the in-app ads.